AB0397 Abatacept shows better sustainability than tnf inhibitors when used following initial biologic dmard failure in the treatment of rheumatoid arthritis: 8 years of real-world observations from the rhumadata® clinical database and registry. (15th June 2017) - Choquette, D; Bessette, L; Alemao, E; Haraoui, B; Massicotte, F; Mtibaa, M; Muratti, E; Pelletier, J-P; Postema, R; Raynauld, J-P; Rémillard, M-A; Sauvageau, D; et al.
Abstract : Background: In the absence of biomarkers predicting response to a specific therapy, the choice of second biologic is based mostly on habit and availability of an alternative agent. Traditionally, a second anti-TNF was the preferred option, but recent registry data point to better responses and retention if a drug with a different mode of action is prescribed. Objectives: Assess the long-term retention of abatacept (ABA) and TNFi following first biologic (b)DMARD inadequate response in RHUMADATA® registry patients (pts) with RA. Methods: Data from RHUMADATA® pts with RA prescribed either ABA or TNFi as the second bDMARD after 1 January 2006 were analysed. Pts were followed until treatment discontinuation or 9 January 2017 cut-off. Pt characteristics were compared using descriptive statistics, bDMARD discontinuation rates using Kaplan-Meier methods, and proportional hazard models were used to identify predictors of treatment discontinuation. Results: Data for 92 and 194 pts prescribed ABA or a TNFi, respectively, as second-line treatment were extracted. No clinically significant differences in baseline characteristics were noted between treatment groups. Most pts were women (76.2%), average age (SD) was 45.1 (13.3) years at diagnosis and disease duration 10.8 (9.0) years. Most pts were stopping an anti-TNF agent: 97% of those who were switched to ABA and 83% of those who were prescribed a second anti-TNF. Overall, 77.6% of pts stopped their first bDMARD after >6 months of treatment (secondary failure). Significant differences in retention between ABA and TNFi groups (log-rank p=0.0002) were observed (Table, Figure). Results remained unchanged for pts treated with TNFi only in first line, and primary/secondary failure of the first bDMARD did not affect sustainability of the second agent. Lack of efficacy (57.7%) and AEs (16.5%) were the most commonly cited reasons for treatment discontinuation. Conclusions: Abatacept has better sustainability over a second line TNFi in RA patients having failed one prior bDMARD. Disclosure of Interest: D. Choquette Consultant for: BMS, Speakers bureau: BMS, L. Bessette Grant/research support from: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Consultant for: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Celgene, Lilly, Novartis, E. Alemao Shareholder of: BMS, Employee of: BMS, B. Haraoui Grant/research support from: BMS, Janssen, Roche, Consultant for: Abbvie, Amgen, BMS, Celgene, Janssen, Merck, Pfizer, Roche, Sandoz, UCB, Speakers bureau: Pfizer, UCB, F. Massicotte: None declared, M. Mtibaa Shareholder of: BMS, Employee of: BMS, E. Muratti Employee of: BMS, J.-P. Pelletier: None declared, R. Postema Shareholder of: BMS, Employee of: BMS, J.-P. Raynauld Speakers bureau: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, Sanofi, Novartis, UCB, M.-A. Rémillard: None declared, D. Sauvageau: None declared, A. Turcotte Consultant for: Amgen, Abbvie, BMS, Celegene, Janssen, Roche, Pfizer, Lilly, Novartis, Merck, Sanofi, UCB, Speakers bureau: Amgen, Abbvie, BMS, Celegene, Janssen, Roche, Pfizer, Lilly, Novartis, Merck, Έ. Villeneuve Speakers bureau: Abbvie, Roche, BMS Consultant - Celgene, Cimzia, Pfizer, L. Coupal: None declared